2017
DOI: 10.1002/cbic.201700210
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Protein Labeling by Paal–Knorr Conjugation

Abstract: The application of new chemical reactions in a biological context has advanced bioconjugation methods for both fundamental research and commercial arenas. Recent adaptations of reactions such as Huisgen 1,3-dipolar or Diels–Alder cycloadditions have enabled the labeling of specific residues in biomolecules by the attachment of molecules carrying azides, alkynes, or strained alkenes. Although these are fundamental tools, there is a need for the discovery of reactions that can label native proteins. We report he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is well known that 2,5-diones can be converted to the corresponding pyrroles under Paal-Knorr conditions in presence of amines 33 39 , while 2,4-diones lead to the formation of pyrazoles when hydrazine or hydrazide nucleophiles are employed 31 , 40 . Nevertheless, reports describing the reaction between 2,5-diones and α-effect nucleophiles (usually performed at high temperatures and under acid catalysis) are scarce and provide poor product characterization 41 45 .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that 2,5-diones can be converted to the corresponding pyrroles under Paal-Knorr conditions in presence of amines 33 39 , while 2,4-diones lead to the formation of pyrazoles when hydrazine or hydrazide nucleophiles are employed 31 , 40 . Nevertheless, reports describing the reaction between 2,5-diones and α-effect nucleophiles (usually performed at high temperatures and under acid catalysis) are scarce and provide poor product characterization 41 45 .…”
Section: Resultsmentioning
confidence: 99%
“…We attribute this to the reduced cross-linking density of the MA-SA composition due to fewer methacrylated groups on each protein. Streptavidin contains 5 NH 2 groups per subunit (20 in total) [ 42 ] whereas bovine serum albumin has ∼30–35 sterically accessible amino groups [ 43 ]. It is important to note that we do not functionalize all accessible amino groups as this would inevitably lead to protein unfolding and loss of bio functionality [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we and other have recently demonstrated that the Paal-Knorr reaction can also readily take place in native biological systems [11][12][13] . More importantly, the Paal-Knorr precursor γ-dicarbonyl resides on many endogenous metabolites and bioactive natural products 14 .…”
mentioning
confidence: 80%